(untitled) (Fiep Bulletin - online, 2015)
Postural problems developed from the adopted positions to the realization of the dentistry professional activity’s are a point of study and preoccupation of several authors. A problem of great importance and little boarded by inquiries, are the occupational complain’s or disturbances of discomfort and / or pain reported during the period of academic formation. Through this survey there were confirmed the presence of pain and / or discomfort, where (80%) are related to the work posture adopted by the academics of the course, as well was established a relation between the realization of clinical specific proceedings and the clinical signs appearance. The clinical proceedings that presented bigger incidence of complaints, for part of the academics, were respectively the next ones: periodontics, endodontics, exodontics, dentístic and proceedings carried out in the subsequent superior arcade.The proceeding identifications of complaint was done through a questionnaire application. Once identified, the principal clinical proceedings of difficulty reported were carried out the analyses of the work postures, during the realization of these proceedings, by the applications program of the Intervals Repetition Method (MRI) and subsequently analyzed through the RULA method. The considered results showed several repeats of movements, embarrassment postures and the ergonomic interventions needed about the conditions of practical apprenticeship of these future dentistry professional’s.